2021
DOI: 10.3389/fimmu.2021.717832
|View full text |Cite
|
Sign up to set email alerts
|

Key Gene and Functional Pathways Identified in Unexplained Recurrent Spontaneous Abortion Using Targeted RNA Sequencing and Clinical Analysis

Abstract: Identifying the mechanisms underlying unexplained recurrent spontaneous abortion (URSA) can help develop effective treatments. This study provides novel insights into the biological characteristics and related pathways of differentially expressed genes (DEGs) in URSA. Nineteen patients with URSA and three healthy fertile women with regular menstruation (control group) were recruited. RNA was extracted from the two groups to determine the differential expression of immunoregulatory gene sequences. Gene ontology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 49 publications
0
14
0
1
Order By: Relevance
“…Studies have shown that TLR was expressed in placental cells and participated in the initiation of signal mediators that were essential for the immune response in choriocarcinoma cell lines, which may be related to placental inflammation ( Klaffenbach et al, 2005 ). Similarly, cytotoxicity mediated by natural killer cells (NK) can lead to endometritis, form a uterine immune state, and then lead to infertility, recurrent abortion, and so on ( Chen et al, 2020 ; Li et al, 2020 ; Gu et al, 2021 ). Other studies have shown that apoptosis can affect the differentiation and invasion of trophoblast cells, block the process of vascular recasting, change the function of the placenta, and finally lead to embryo implantation, growth restriction, and abortion ( Sharp et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that TLR was expressed in placental cells and participated in the initiation of signal mediators that were essential for the immune response in choriocarcinoma cell lines, which may be related to placental inflammation ( Klaffenbach et al, 2005 ). Similarly, cytotoxicity mediated by natural killer cells (NK) can lead to endometritis, form a uterine immune state, and then lead to infertility, recurrent abortion, and so on ( Chen et al, 2020 ; Li et al, 2020 ; Gu et al, 2021 ). Other studies have shown that apoptosis can affect the differentiation and invasion of trophoblast cells, block the process of vascular recasting, change the function of the placenta, and finally lead to embryo implantation, growth restriction, and abortion ( Sharp et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found that m 6 A modification in RSA trophoblast cells was significantly different from that in the normal control group through MeRIP-seq, and the pathways of the differential m 6 A modified genes enriched have been reported to be related to the pathogenesis of RSA such as toll-like receptor signaling pathway, natural killer cell–mediated cytotoxicity, and necrotizing apoptosis. ( Klaffenbach et al, 2005 ; Sharp et al, 2010 ; Chen et al, 2020 ; Li et al, 2020 ; Gu et al, 2021 ). The authors pointed out that URSA patients, compared with normal pregnant women, were enriched in several signaling pathways associated with immune regulatory functions, including natural killer cell–mediated cytotoxicity, cytokine receptor interaction, and other signaling pathways which were consistent with our findings ( Klaffenbach et al, 2005 ; Sharp et al, 2010 ; Chen et al, 2020 ; Li et al, 2020 ; Gu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, some researchers have obtained some results about recurrent abortion through transcriptome sequencing [ 27 , 28 ]. In this study, we firstly performed transcriptome sequencing analysis on the tissues of 3 patients with RSA and 3 patients with normal abortion, and found key molecules by constructing lncRNA-related ceRNA network, which is helpful to explore the pathogenic mechanism of RSA.…”
Section: Discussionmentioning
confidence: 99%
“…According to statistics, over 5% of women at reproductive age su er from RSA [3]. Multiple pathological factors lead to RSA, including genetic factors, anatomical abnormalities, endocrine disorders, infectious diseases, and thyroid dysfunction [4,5]. Embryonic chromosomal abnormality is the main cause of spontaneous abortion in early pregnancy, which results in over 50% of rst trimester miscarriages [6][7][8].…”
Section: Introductionmentioning
confidence: 99%